Super Mario Logic: um jogo sério para lógica de programação - Panegalli, Felipe Schmitt (2016)
This project is part of the Graduate Program in Educational Technology, Development of Educational Technologies and it aims at developing, as a final product, a Serious Game named Super Mario Logic in order to help in the teaching and learning process of logic programming which is essential to the professional future of the area. It is through logic programming that students learn to develop algorithms, which are sequences of steps used to reach a specific result. From the development of algorithms there are the programming stages, in which a significant study of logic programming and algorithms plays a key role for the programmer. This project aims at developing a serious game that challenges students into solving problems in logic programming. Serious games are becoming popular as they help students learn, making them interact and learn in an educational and playful way beyond the traditional teaching pattern. The game is being developed through a methodology called INTERAD, which is used for the development of Educational Interfaces.